The Portrayal of Colored People in Harper Lee’s To Kill a Mockingbird (1960) - Muhammad Aziz Nurdinsyah; Didi Sukyadi; Budi Hermawan (Universitas Pendidikan Indonesia (UPI), 2020)
This study is a transitivity analysis of the novel To Kill a Mockingbird by Harper Lee (1960). This study aims to investigate representation of a colored man named Tom Robinson through the types of process related to Tom Robinson. By using qualitative research, the research used the theory of Transitivity proposed by Halliday (1994). The data sources were in the form of eighteen clauses that specifically represent Tom Robinson and were sorted by concordance software Antconc 3.8.1. The findings of the research showed that there are four processes found in the clauses related to the character. Material process is the most frequent process (50%) followed by Relational process (27%) which are divided into two: Attributive Relational process (22%) and Identifying Relational Process (5%), Mental process (17%), and Verbal process (7%) are the second lowest and least frequent type in this research. The result of the research indicates that Tom Robinson as one of the people of color in the novel To Kill a Mockingbird is represented as a man who experienced social injustice.Keywords: Representation, Systemic Functional Linguistics, Ideational Meaning, Transitivity